Feminism in France (RLE Feminist Theory) : From May '68 to Mitterand. - Duchen, Claire (Routledge library editions. Feminist theory., 2012)
Feminism in France charts the evolution of the women's liberation in France (MLF) from its emergence in 1968 to the present. Claire Duchen provides a lucid and compelling account of different feminist practices in France, clarifying the divergent political stances and the feminist theory that informs them. The remarkably clear introduction to French feminist theory, notably of Luce Irigaray and Helene Cixous, places it in its wider intellectual and political context and illuminates the complex connection of feminist thinking to other strands of contemporary French thought, represen.